2002
DOI: 10.1126/science.1067389
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone Suppression of α-Synuclein Toxicity in a Drosophila Model for Parkinson's Disease

Abstract: Parkinson's disease is a movement disorder characterized by degeneration of dopaminergic neurons in the substantia nigra pars compacta. Dopaminergic neuronal loss also occurs in Drosophila melanogaster upon directed expression of alpha-synuclein, a protein implicated in the pathogenesis of Parkinson's disease and a major component of proteinaceous Lewy bodies. We report that directed expression of the molecular chaperone Hsp70 prevented dopaminergic neuronal loss associated with alpha-synuclein in Drosophila a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
911
3
8

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,206 publications
(966 citation statements)
references
References 20 publications
44
911
3
8
Order By: Relevance
“…We demonstrate that specific HSP molecular chaperones immunolocalize with a-synuclein in LB in substantia nigra. These findings are in agreement with the recent report that Lewy body inclusions in Parkinson's disease and related disorders are immunopositive for Hsp70 and Hsp40 (Auluck et al 2002).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We demonstrate that specific HSP molecular chaperones immunolocalize with a-synuclein in LB in substantia nigra. These findings are in agreement with the recent report that Lewy body inclusions in Parkinson's disease and related disorders are immunopositive for Hsp70 and Hsp40 (Auluck et al 2002).…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, torsinA immunoreactivity has been previously demonstrated in LB of PD and DLB patients (Shashidharan et al 2000;Sharma et al 2001) and we demonstrate here that a-synuclein immunopositive inclusions are also torsinA immunoreactive in a cell culture model. Furthermore, Hsp70 has recently been demonstrated to colocalize to LB in Drosophila brain and Hsp70 and Hsp40 were found to localize with LB in human brain (Auluck et al 2002). In agreement with this study, we found that Hsp70 and Hsp40 family members, HDJ-1 and HDJ-2, localized with LB in human DLB brain.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hsp70 members are highly multifunctional proteins that have been shown to play a key role in proteome maintenance, such as in de novo protein folding (co-or post-translational), protein translocation across membranes (Lyman and Schekman, 1997;Matlack et al, 1999;Young et al, 2003), refolding of stress damaged proteins (Ben-Zvi et al, 2004;Schroder et al, 1993;Sharma et al, 2010), in preventing protein aggregation (Auluck et al, 2002;Broadley and Hartl, 2009;Klucken et al, 2004;Sakahira et al, 2002;Warrick et al, 1999), disaggregation (Ben-Zvi and Goloubinoff, 2001;Diamant et al, 2000;Liberek et al, 2008;Shorter, 2011) and degradation of irreparable misfolded proteins (Bercovich et al, 1997;Fisher et al, 1997;Urushitani et al, 2004). These essential and diverse cellular functions of Hsp70 are attributed to its physical interaction with various co-chaperones such as Hsp40, NEFs and with proteins such as HIP, HOP and CHIP.…”
Section: Ii41121 the Hsp70 Chaperone Systemmentioning
confidence: 99%
“…37 Work in Drosophila may accelerate understanding of the human disease by identifying candidate pathways for disease modification. 38 The genetic forms of PD are uncommon, but gene therapy targeting the a-synuclein, Parkin or other pathways may also turn out to be an appropriate intervention for idiopathic PD. Using a-synuclein transgenic mice, it was shown that overexpression of b-synuclein prevented aggregation of a-synuclein and the resulting abnormal phenotype.…”
Section: Stem Cells May Be Driven To Differentiate Into Functioning Dmentioning
confidence: 99%